PECULIARITIES OF GENERATION OF BVI-NOISE OF A HELICOPTER ROTOR IN “VORTEX RING” MODE - Lukianov, P. V. (Computer Science and Applied Mathematics, 2022)
During the vertical, or almost vertical, descent of the helicopter around the rotor, a toroidal “vortex ring” is formed. Sufficient attention has been paid to the study of aerodynamic parameters of the flow in this flight mode. The change of the main power characteristics of the helicopter operation in the “vortex ring” mode is investigated. However, for a more detailed study of this mode, it is necessary to have information about the sound field that is formed during the interaction of the helicopter rotor with the “vortex ring”. The following problem arises: how does the “vortex ring” affect the process of sound generation, its partial transformation into vibration? In this work, the problem of generating BVI noise in the “vortex ring” mode is formulated and numerically solved. The overall problem consists of aerodynamic and acoustic parts. The aerodynamic part of the problem includes the system of Euler and continuity equations. The acoustic part of the problem consists of a system of equations previously obtained by the author that describes the process of sound generation and propagation. On its basis, the near sound field was studied. The numerical calculation of the far sound field is based on the integral representation. The model used in this work is considered to be transitional, approximate, since the intense vibrations arising on the surface are not small values. Since today there are no models that allow you to simultaneously correctly describe sound and vibration, the model of sound generation is used in the work as a transitional one. Despite the fact that a priori only small acoustic disturbances are taken into account in it, nevertheless, it allows one to approach the description of vibrations. Analysis of dimensionless density pulsations suggests that in the rotor operating mode “vortex ring” 3-4 series of transverse vibrations are realized on the blade surface. These lateral vibrations are quite a dangerous phenomenon, since they can lead to intense bending vibrations of the blade, its destruction on the flutter. At the same time, the area where these vibrations are realized is significantly larger than for the case of an airplane landing of a helicopter. The degree of blade bending makes the vibration region more compact for a blade with a large bend. The noise generated in this case has a low-frequency nature 10-20 dB higher than the noise of an airplane landing of a helicopter. Its main energy is concentrated in the first 7-8 harmonics, which is significantly amplified by the vibrational leaving noise. These features make it possible to identify the “vortex ring” mode, which in practice allows further improvement of the flight safety system.